Serum SP-A and KL-6 levels can predict the improvement and deterioration of patients with interstitial pneumonia with autoimmune features - Wang, Jingxian (BMC Pulm Med, 2020)
BACKGROUND: Some patients with interstitial pneumonia with autoimmune features (IPAF) showed a progressive course despite therapy. This study aimed to evaluate whether serial changes in the serum levels of surfactant protein-A (SP-A) and Krebs von den Lungen-6 (KL-6) can predict disease progression. METHODS: Sixty-four patients with IPAF and 41 patients with non-fibrotic lung disease (non-FLD) were examined. Based on long-term changes in lung function, 36 IPAF patients who were followed up for more than 3 months were divided into a progressive group (n = 9), an improvement group (n = 13), and a stable group (n = 14). Serum KL-6 and SP-A levels were measured. The sensitivity, specificity, cut-off value, and area under the curve (AUC) value for each of the indices were determined using receiver operating characteristic (ROC) curve analysis. The expression differences in these biomarkers and their correlation with disease severity were analyzed. RESULTS: Compared with non-FLD patients, serum SP-A and KL-6 levels in IPAF patients were increased significantly [SP-A: (p < 0.001); KL-6: (p < 0.001)] and negatively correlated with DLCO (SP-A: r(S) = − 0.323, p = 0.018; KL-6: r(S) = − 0.348, p = 0.0011). In patients with progressive disease, the posttreatment serum SP-A and KL-6 levels were increased significantly compared with pretreatment levels [SP-A: (p = 0.021); KL-6: (p = 0.008)]. In patients showing improvement, the levels were decreased significantly [SP-A (p = 0.007) and KL-6 (p = 0.002)]. Changes in serum biomarkers (Delta SP-A and Delta KL-6) were significantly negatively correlated with changes in lung function (Delta FVC, Delta DLCO and Delta FEV1) (r(S) = 0.482, p < 0.05). A significant positive correlation was found between Delta SP-A and Delta KL-6 (r(S) = 0.482, p < 0.001). CONCLUSIONS: Serum SP-A and KL-6 offer high sensitivity and specificity for the diagnosis of IPAF. The decrease in serum SP-A and/or KL-6 levels in patients with IPAF is related to the improvement in pulmonary function. SP-A and KL-6 may be important biomarkers for predicting disease progression in patients with IPAF.